Dual-axes confocal microscopy with post-objective scanning and low-coherence heterodyne detection - Wang, Thomas D. (2003)
We present a dual-axes confocal microscope that employs postobjective scanning and low-coherence heterodyne detection to collect vertical cross-sectional images from biological tissue with high axial resolution, reduced noise from scattered light, deep tissue penetration, and a large dynamic range. This architecture can be scaled down to millimeter dimensions with microelectromechanical systems technology for performance of in vivo optical biopsy.